Soil aggregate size-dependent relationships between microbial functional diversity and multifunctionality. (March 2021) - Han, Shun; Delgado-Baquerizo, Manuel; Luo, Xuesong; Liu, Yurong; Van Nostrand, Joy D.; Chen, Wenli; Zhou, Jizhong; Huang, Qiaoyun
Abstract: Soil stability and aggregates are important drivers of soil fertility and microbial diversity and are highly vulnerable to land degradation. However, the role of soil aggregates in driving the responses of microbial functional diversity and multiple ecosystem services and functions (multifunctionality) to further degradation (e.g., fertilization) remains largely unexplored and poorly understood. In this study, we used soils from long-term experiments involving inorganic and organic fertilization treatments to investigate the role soil aggregates (microscale) play in driving microbial functional gene diversity (via GeoChip) and the activity of multiple extracellular enzymes in an agricultural ecosystem. We found that microbial functional gene diversity has a significant and positive relationship with soil multifunctionality, which is enhanced in soil aggregates by organic fertilizer but is reduced by inorganic fertilizer. We also found that soil aggregate fractions indirectly controlled multiple ecosystem functions via changes in functional diversity. Smaller soil aggregates with higher resource availability (carbon and nitrogen) supported more ecological functions than larger aggregates under contrasting fertilizer management regimes. Soil multifunctionality is regulated by the differences in resource availability and not by microbial functional gene composition, which suggests that microbial functional diversity contributed more to multifunctionality than gene composition. Random forest analysis and structural equation modeling indicated that soil carbon and nitrogen and microbial functional diversity together determined the multifunctionality, whereas soil traits have more standardized total effects than functional diversity. Our study highlights that soil aggregation stratifies soil nutrition and microbial functional diversity, which leads to the differentiation of aggregate ecosystem multifunctionality. Highlights: Microbial functional diversity positively regulates soil multifunctionality. Microbial diversity contributes more to multifunctionality than taxonomic traits. Soil aggregate size may indirectly and negatively determine multifunctionality. Organic and inorganic fertilizers have opposite effects on multifunctionality. Soil nutrition and functional diversity together control multifunctionality.